2019
DOI: 10.5688/ajpe6967
|View full text |Cite
|
Sign up to set email alerts
|

An Elective Course in Lesbian, Gay, Bisexual, and Transgender Health and Practice Issues

Abstract: Objective. To design, implement and assess a lesbian, gay, bisexual, and transgender (LGBT) health and practice elective course for second-and third-year Doctor of Pharmacy (PharmD) students. Methods. The course focused on health promotion, health care barriers, disease prevention, and treatment throughout an LGBT person's lifespan. The course included topic discussions, reading assignments, various active-learning activities, an objective structured clinical examination (OSCE) with a transgender person, and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…LGBT curricular education are important factors for healthcare professional students' cultural competency. This finding is akin to the few studies that have shown that curricular education can be effective in ameliorating LGBT-specific attitudes, preparedness, and knowledge among dental, [18] medical, [7,8] and pharmacy [19,20] students. As such, both local and national educational initiatives should advocate for these experiential variables.…”
Section: Plos Onementioning
confidence: 68%
“…LGBT curricular education are important factors for healthcare professional students' cultural competency. This finding is akin to the few studies that have shown that curricular education can be effective in ameliorating LGBT-specific attitudes, preparedness, and knowledge among dental, [18] medical, [7,8] and pharmacy [19,20] students. As such, both local and national educational initiatives should advocate for these experiential variables.…”
Section: Plos Onementioning
confidence: 68%
“…18,40 One pharmacy program implemented objective structured clinical examination (OSCE) of hormone therapy with a transgender patient to allow students to demonstrate their knowledge in a safe environment. 23 Team-based learning may also be incorporated through case-based questions within a pharmacy skills-based laboratory course, but students may miss the opportunity to practice their individual counseling skills. 32 These practice-based activities may be coordinated with content taught in a therapeutics  Library of videos and resources for incorporating LGBTQIA+ health into medical school curricula LavenderHealth 46  Blog that provides free information that can be used across education programs and levels to introduce basic LGBTQ care concepts to students and practitioners  Includes sample active learning activities and syllabi Health professional best practices Gay and Lesbian Medical Association (GLMA) [47][48][49] …”
Section: Skills-based Laboratory Coursesmentioning
confidence: 99%
“…Elective courses dedicated to this topic improved student knowledge and confidence in LGBTQIA+ content. 23,24,26 An elective course may allow for additional opportunities for active learning and ongoing exposure to the content over the course of a semester. 23,24,26 For example, students may participate in topic discussions, take part in counseling sessions with a transgender patient, and hear from guest speakers from the LGBTQIA+ community.…”
Section: Developing An Elective Coursementioning
confidence: 99%
“…A total of 63 unique articles were initially retrieved, of which 15 specifically addressed issues directly relevant to the role of pharmacists in TG health care. 13,18–31 Additional references (one journal article 32 and five web-based articles 6,10,33–35 ) were identified by searching electronic databases (Google Scholar, Google, Science Direct, and Cochrane Database of Systematic reviews) and by manually searching the reference lists of identified articles. Other secondary searches (for various subsections) were also performed utilizing the terms transgender or gender dysphoria or gender identity disorder and epidemiology, etiology, disease management, diagnosis, cultural competency, pharmacotherapy, health care, human immunodeficiency virus, sexually transmitted disease, and antiretroviral therapy.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, an elective two-credit course on LGBT health care was implemented at UNT System School of Pharmacy focusing on health promotion, identifying barriers to health care, and health care resources for LGBT persons (Table 2). 32 Several guest speakers from the LGBT community participated in the course. The comparison of the pre- vs. postcourse seven learning objectives (e.g., summarizing health care resources for LGBT persons) reported significant improvement ( p <0.001) in the students.…”
Section: Inclusion Of Lgbt Topics Into the Pharmacy Curriculummentioning
confidence: 99%